2015
DOI: 10.1007/s12020-015-0588-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin is associated with peripheral nerve function in patients with type 2 diabetes

Abstract: The aim of this study is to investigate the association between serum albumin concentrations and nerve conduction (NC) parameters in Chinese patients with type 2 diabetes (T2DM). A total of 409 T2DM patients were enrolled between October 2010 and April 2014. All participants underwent nerve conduction studies. The composite Z scores for NC parameters including conduction velocity (CV), amplitude, and latency were calculated as well. Serum albumin was measured by Bromcresol Green dye-binding method. The composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
5
26
0
Order By: Relevance
“…The inflammation, coagulation and nutrition are associated with DPN occurrence and development (9,10,11,12,15,17). The present study finds the first evidence in suggesting that PFR is closely related with DPN in T2DM.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The inflammation, coagulation and nutrition are associated with DPN occurrence and development (9,10,11,12,15,17). The present study finds the first evidence in suggesting that PFR is closely related with DPN in T2DM.…”
Section: Discussionsupporting
confidence: 60%
“…Secondly, ALB is an important nutritional biomarker as well as an inflammatory marker (16). Li et al suggested that serum ALB was independent with the peripheral nerve function in T2DM, especially to those T2DM patient albuminuria (17). In addition, recent studies have reported that PALB is served as another important biomarker for nutritional status and it is more sensitive to malnutrition than ALB (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral nerve function was evaluated by NCS with the use of the EMG Myto, EBNeuro (ESAOTE, Florence, Italy), which has been described previously41. Briefly, NCS were performed by experienced electrophysiologists who were unaware of the laboratory results.…”
Section: Methodsmentioning
confidence: 99%
“…Abnormal NC was defined by abnormality of one or more parameters in two or more tested anatomical nerves42. Composite z scores of CV, amplitude, and latency were constructed as previously described4143.…”
Section: Methodsmentioning
confidence: 99%